Integrasi sebagai wacana teoritis dalam kajian sosial politik Indonesia - Maftuh, Abdul Aziz (Maliki Interdisciplinary Journal, 2026)
This paper examines social integration as a theoretical discourse within the socio-political context of Indonesia. The main issue addressed is the normative use of the term “integration” without a sufficient conceptual foundation, resulting in public policies that fail to address structural inequalities. This study employs a descriptive qualitative approach through library research to map theoretical frameworks on integration, including functionalism, conflict theory, pluralism, multiculturalism, and critical citizenship. The analysis synthesizes these frameworks to evaluate their relevance to Indonesian society. Findings indicate that integration is a dynamic process involving power relations, identity recognition, resource distribution, and civic participation. Therefore, effective integration must combine shared values, social justice, cultural recognition, and inclusive public spaces. The study concludes that meaningful integration cannot rely on assimilationist approaches but requires multidimensional strategies rooted in social justice.